2017
DOI: 10.4049/jimmunol.1601989
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Human Malaria Infection Leads to Long-Lasting Changes in Innate and Innate-like Lymphocyte Populations

Abstract: Animal model studies highlight the role of innate-like lymphocyte populations in the early inflammatory response and subsequent parasite control following Plasmodium infection. IFNγ production by these lymphocytes likely plays a key role in the early control of the parasite and disease severity. Analyzing human innate-like T cell and natural killer (NK) cell responses following infection with Plasmodium has been challenging since the early stages of infection are clinically silent. To overcome this limitation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 65 publications
4
39
1
Order By: Relevance
“…The crosstalk of NK cells and macrophages with effector T cells controlling P. falciparum ‐infected erythrocytes was further emphasized before the emergence of the ILC paradigm. Mpina et al reported interesting data from blood samples from a controlled human malaria infection (CHMI) study with P. falciparum sporozoites in a Tanzanian cohort with volunteers showing an altered composition of the innate‐like lymphocyte compartment including NK, NKT and mucosal‐associated invariant T (MAIT) cells. The data of this controlled infection suggest the emergence of long‐lasting changes of the human innate‐like lymphocyte compartment .…”
Section: Role Of Ilcs In Hcmmentioning
confidence: 99%
See 1 more Smart Citation
“…The crosstalk of NK cells and macrophages with effector T cells controlling P. falciparum ‐infected erythrocytes was further emphasized before the emergence of the ILC paradigm. Mpina et al reported interesting data from blood samples from a controlled human malaria infection (CHMI) study with P. falciparum sporozoites in a Tanzanian cohort with volunteers showing an altered composition of the innate‐like lymphocyte compartment including NK, NKT and mucosal‐associated invariant T (MAIT) cells. The data of this controlled infection suggest the emergence of long‐lasting changes of the human innate‐like lymphocyte compartment .…”
Section: Role Of Ilcs In Hcmmentioning
confidence: 99%
“…Mpina et al reported interesting data from blood samples from a controlled human malaria infection (CHMI) study with P. falciparum sporozoites in a Tanzanian cohort with volunteers showing an altered composition of the innate‐like lymphocyte compartment including NK, NKT and mucosal‐associated invariant T (MAIT) cells. The data of this controlled infection suggest the emergence of long‐lasting changes of the human innate‐like lymphocyte compartment . Therefore, the innate immune response on host immunity with recurrent parasite infection and associated pathologies requires more investigations which include human ILCs.…”
Section: Role Of Ilcs In Hcmmentioning
confidence: 99%
“…Overall, it has become clear that there is more heterogeneity in the MAIT cell population than initially appreciated[45]. A small fraction of MAIT cells isolated from the blood can also secrete IL-17 ex vivo following short term stimulation with via CD3/CD28 or PMA and ionomycin[12,46,47]. It is noteworthy that a large fraction of MAIT cells in the blood expresses the transcription factor RORγt[37], which drives T-cells towards IL-17 production[48].…”
Section: Mait Cell Subsets Phenotypes and Function In Bloodmentioning
confidence: 99%
“…Finally, MAIT cells in the blood can be divided into different subsets based on CD8 and CD4 co-receptor expression. The relationship of these subsets is unclear, but single cell gene expression analysis from the two major MAIT subsets, CD8 + and CD8 − (CD4 − ) cells, isolated from the blood demonstrated distinct transcriptional differences[44] and their respective frequencies can change independently following infection[46]. …”
Section: Mait Cell Subsets Phenotypes and Function In Bloodmentioning
confidence: 99%
See 1 more Smart Citation